2011
DOI: 10.1371/journal.pone.0023528
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically Clustered Extinction Risks Do Not Substantially Prune the Tree of Life

Abstract: Anthropogenic activities have increased the rate of biological extinction many-fold. Recent empirical studies suggest that projected extinction may lead to extensive loss to the Tree of Life, much more than if extinction were random. One suggested cause is that extinction risk is heritable (phylogenetically patterned), such that entire higher groups will be lost. We show here with simulation that phylogenetically clustered extinction risks are necessary but not sufficient for the extensive loss of phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 53 publications
3
48
2
Order By: Relevance
“…That species facing elevated extinction risk are not concentrated in particular parts of the phylogeny is no cause for optimism, however, as recent simulations have shown that other factors are involved in determining the magnitude of PD loss during extinctions [123]. In particular, trees derived from real data generally have asymmetric topologies [124][128]; the coral supertree is no exception (P<0.001, Colless' [129] index significantly greater than predicted by the Yule model).…”
Section: Discussionmentioning
confidence: 94%
“…That species facing elevated extinction risk are not concentrated in particular parts of the phylogeny is no cause for optimism, however, as recent simulations have shown that other factors are involved in determining the magnitude of PD loss during extinctions [123]. In particular, trees derived from real data generally have asymmetric topologies [124][128]; the coral supertree is no exception (P<0.001, Colless' [129] index significantly greater than predicted by the Yule model).…”
Section: Discussionmentioning
confidence: 94%
“…Observations for greater than random losses of phylogenetic diversity that have been inferred for many clades under realistic extinction scenarios likely refl ect the particularities of phylogenetic tree topology in combination with a tendency for more extinction prone species to fall within species poor clades (Heard and Mooers 2000 ;von Euler 2001 ;Parhar and Mooers 2011 ). There does seem to be a general trend within some clades for threatened species to be overrepresented in speciespoor clades (e.g.…”
Section: Quantifying the Loss Of Evolutionary Historymentioning
confidence: 97%
“…2 ). However, in a more recent study, again using simulations, but this time assuming both a more realistic model of diversifi cation and a range of phylogenetic signal in extinction probabilities, Parhar and Mooers ( 2011 ) suggested that the loss of phylogenetic diversity under phylogenetically non-random extinctions was more or less indistinguishable from random (see also Heard and Mooers 2000 ). Seemingly, the observation of phylogenetic signal in extinction risks and the non-random loss of phylogenetic diversity are not necessarily connected directly.…”
Section: Quantifying the Loss Of Evolutionary Historymentioning
confidence: 99%
“…While extinction prunes the tree of life non-randomly, the loss of evolutionary history, measured in phylogenetic branch lengths scaled in millions of years, is not always greater than predicted by chance [55,68]. In addition, the loss of PD does not always correlate with the loss of feature diversity [42], and recent work suggests there may be a scale dependence in the correlation between phylogenetic distance and feature similarity [41].…”
Section: Extinction and The Loss Of Feature Diversitymentioning
confidence: 99%